Forced degradation of metronidazole, oxytetracycline and furazolidone studies using High Performance Liquid Chromatography - Violeta Tauber (Giugiu),; Viorica Chiurciu (Medicamentul Veterinar, 2014)
The study describes the development of a HPLC -DAD method for the estimation of oxytetracycline and furazolidone in Enteroguard M - powder. The proposed method utilizes a Betasil C 18 column, (4.6 x 250 mm, 5 µm), at 300 C, optimum mobile phase consisted of 40 mM phosphate buffer (pH=7.5): methanol in gradient elution. The flow rate was optimized to 1mL/min and the detection was carried at 254 nm. The drug substance was exposed to temperature, light, oxidants, acid and basic hydrolysis, and the resultant samples were analyzed by the proposed method.